Novel Approaches for the Management of Type 2 Diabetes Mellitus: An Update - Kumar, Abhishek; Mazumder, Rupa; Rani, Anjna; Pandey, Pratibha; Khurana, Navneet (Current Diabetes Reviews, 2024)
Diabetes mellitus is an irreversible, chronic metabolic disorder indicated by hyperglycemia. It is now considered a worldwide pandemic. T2DM, a spectrum of diseases initially caused by tissue insulin resistance and slowly developing to a state characterized by absolute loss of secretory action of the β cells of the pancreas, is thought to be caused by reduced insulin secretion, resistance to tissue activities of insulin, or a combination of both. Insulin secretagogues, biguanides, insulin sensitizers, alpha-glucosidase inhibitors, incretin mimetics, amylin antagonists, and sodium-glucose co-transporter-2 (SGLT2) inhibitors are the main medications used to treat T2DM. Several of these medication’s traditional dosage forms have some disadvantages, including frequent dosing, a brief half-life, and limited absorption. Hence, attempts have been made to develop new drug delivery systems for oral antidiabetics to ameliorate the difficulties associated with conventional dosage forms. In comparison to traditional treatments, this review examines the utilization of various innovative therapies (such as microparticles, nanoparticles, liposomes, niosomes, phytosomes, and transdermal drug delivery systems) to improve the distribution of various oral hypoglycemic medications. In this review, we have also discussed some new promising candidates that have been approved recently by the US Food and Drug Administration for the treatment of T2DM, like semaglutide, tirzepatide, and ertugliflozin. They are used as a single therapy and also as combination therapy with drugs like metformin and sitagliptin.
Keywords: antidiabetic